Pengaruh Celebrity Endorsement, WOM dan Harga Terhadap Keputusan Pembelian Produk Zara di Kota Semarang - Adiyaksa Putra Hutama; Imam Nuryanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The need for clothing not only fulfills primary needs but can also provide self-confidence for fashion users. Zara is one of the fashion brands that presents high quality and product designs that support all activities. However, the increasingly tight competition in the industrial world demands that companies be more creative and make products more competitive. This study aims to analyze the influence of celebrity endorsement, word of mouth, and price on purchasing decisions for Zara products in Semarang City. This research is quantitative and involves a population of consumers who have purchased Zara products at least once. The research method used is a survey, with purposive sampling technique, where 115 respondents were selected based on certain criteria. The data collected was analyzed using multiple linear regression test with the help of SPSS software. The results of this study show that celebrity endorsement has a significant positive influence on purchasing decisions, word of mouth has a significant positive influence on purchasing decisions, and price has a significant positive influence on purchasing decisions.